Atomistic simulation and interatomic potential comparison in α-Al2O3: lattice, surface and extended-defects properties. (1st April 2022) - Xu, Qinqin; Salles, Nicolas; Chevalier, Jérome; Amodeo, Jonathan
Abstract: Aluminum oxide ( α -Al2 O3 ) is known as one of the major ceramic oxide and is currently used for its advanced mechanical properties. Nowadays, it requires a more in-depth description at small-scales especially for applications in the fields of nanocrystalline ceramic fabrication and nanomechanics. In this study, we investigate the transferability of several types of interatomic potentials including rigid ion, 2/3-body and many-body variable charge models. In particular, a special attention is paid to the material properties that are the most relevant for nanomechanical applications such as lattice properties, surface and stacking fault energies as well as dislocation modeling. Simulation outcomes are compared to reliable DFT simulations and most up-to-date experiments available from the literature.